A Study on Dynamic Weighted Failure Entropy of Order α. Issue 2 (3rd April 2017) - Nair, Rohini S.; Abdul-Sathar, E. I.; Rajesh, G.
SYNOPTIC ABSTRACT: Abbasnejad (2011 ) proposed new measures of information known as failure and dynamic failure entropy of order α based on generalization of the well-known cumulative entropy. In this article, we propose the weighted forms of failure entropy (WFE) and dynamic failure entropy (DWFE) of order α. Some relationships of these measures with well-known reliability measures and ageing classes are studied and some characterization results for reflected Weibull distribution are provided. We also propose an empirical estimator for the WDFE of order α. We demonstrate the performance of the proposed estimator with a real life data set and further carried out a comprehensive Monte-Carlo simulation study.